Multi-dimensional aspects of mindfulness: psychometric evaluation, neurobiological underpinnings, and experiential insights - Duffy, John R., author; Thomas, Michael L., advisor; Davalos, Deana, committee member; Graham, Dan, committee member; Stephans, Jaclyn, committee member (Colorado State University. Libraries, 2024)
Objective: This dissertation aimed to deepen our understanding of mindfulness by exploring a psychometric evaluation of self-report scales, neurobiological underpinnings, and experiential insights in a multidimensional approach. The objective encompassed three specific aims: firstly, to evaluate the psychometric effectiveness of two self-report scales; the Mindful Attention Awareness Scale (MAAS) and the Five Facet Mindfulness Questionnaire (FFMQ) within populations diagnosed with post-traumatic stress disorder (PTSD), ensuring these tools' validity and reliability while addressing the complexity of mindfulness. Secondly, the research intended to synthesize existing literature on brain networks related to mindfulness through an umbrella review (a review of reviews / metanalyses), aimed to clarify the neural mechanisms of mindfulness. Thirdly, the study used functional magnetic resonance imaging (fMRI) to compare brain activity between a control group performing a visualization task (control) and a group engaged in a guided compassion meditation (experimental). This comprehensive framework sought to advance the field of mindfulness research by integrating psychometric analysis, brain network review synthesis, and experimental neuroimaging to enhance theoretical understanding of mindfulness. Method: We employed a three-pronged methodological approach. Firstly, a psychometric evaluation of the Mindful Attention Awareness Scale (MAAS) and the Five Facet Mindfulness Questionnaire (FFMQ) to assess their reliability and validity in a PTSD-affected veteran population. Secondly, we conducted an umbrella review to synthesize existing research on brain networks and connectivity related to mindfulness to map out neural correlates and their implications. Thirdly, an experimental study using functional magnetic resonance imaging (fMRI) compared neural activation patterns between participants engaged in a visualization task and those practicing guided compassion meditation, aimed to identify distinct neural activities associated with this mindfulness practices. Results: The psychometric evaluation of the MAAS and FFMQ confirmed their validity and reliability in assessing mindfulness in PTSD populations, highlighting mindfulness as a complex, multifaceted construct. An umbrella review of existing literature demonstrated the significant impact of mindfulness on brain connectivity, particularly in the DMN, CEN, and SN networks. The experimental fMRI study revealed distinct neural activation patterns between compassion mindfulness and a visualization task, with compassion mindfulness showing decreased activity in regions involved in emotional regulation and cognitive functions, such as the medial superior prefrontal cortex and anterior cingulate cortex. Conclusions: These findings affirm the utility of MAAS and FFMQ reliability and validity, but demand more nuanced research based on a more multifaceted concept of mindfulness. The impact of mindfulness on large-scale brain networks underscores its potential to enhance cognitive and emotional regulation through neuroplasticity. However, significant methodological variability across studies calls for standardized research protocols to ensure consistency and reliability. Future research should address these limitations, explore the long-term effects of mindfulness, and include diverse populations to improve the generalizability of mindfulness-based interventions. Finally, significant differences in neural activation patterns between visualization tasks and compassion mindfulness meditation, indicate that such mindfulness practices may uniquely influence brain regions associated with emotional regulation and cognitive processes. These findings highlight the potential of compassion mindfulness to modulate brain activity in these areas, offering insights into its mechanisms and benefits.
Keywords: fMRI; neurobiology; PTSD; mindfulness; connectivity; psychometrics